MEMBANGUN KEMAMPUAN SPASIAL LEWAT PELATIHAN PEMETAAN DENGAN TEKNOLOGI DRONE - Okto Supratman; Wahyu Adi; Guskarnali Guskarnali; Okto Supratman (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Drone technologys are now widely used not only for taking photos, videos, but also for mapping. Therefore, it is necessary to conduct mapping training activities with drone technology so that participants can improve their competence in using drones for mapping. Training purposes are 1) To provide an understanding of spatial knowledge through training with drone technology, 2) To increase competence related to Mapping using drones and 3) To produce high resolution maps. The methods or stages of training activities are 1) Coordination of training implementation with cooperation partners, 2) Preparation of training materials, 3) Opening of registration, 4) Opening of Training Classes, 5) Training of spatial data retrieval using drones, 6) Training of Spatial Data Processing from Drones. The results of the mapping training activity with drone technology were attended by 73 participants, of which 29 participants were declared passed and received certificates. Participants who passed were participants who had followed all the training materials and submitted aerial photography and contour maps assignments. Mapping training activities are carried out in online and offline blended learning. Online activities are carried out when opening classes, delivering material, processing data and closing classes, while offline activities are when the practice of taking aerial photos using drones will be used as data processing material. In addition, the results of the training activities include aerial photo maps and high-resolution contour maps from aerial photographs with drones made by training participants.